Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21037/gs-20-699
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and risk factors of central compartment lymph node metastasis in cN0 papillary thyroid carcinoma coexistent with Hashimoto’s thyroiditis

Abstract: Background: Currently, there are few studies on the characteristics of lymph node metastasis in the central region in patients with preoperative negative lymph node (cN0) papillary thyroid carcinoma (PTC) coexistent with Hashimoto's thyroiditis (HT). There is still a significant controversy on whether to perform prophylactic central compartment lymph node dissection for T1/T2 cN0 PTC. Therefore, we aimed to investigate the characteristics and risk factors of central compartment lymph node metastasis in cN0 PTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…Our study also indicated that the TSH in HT patients was higher than that in patients with PTC alone. These results were consistent with many other previous observations ( 24 , 30 ). HT, which is characterized by the infiltration of abundant lymphocytes, fibrosis, and parenchymal atrophy of thyroid tissue, is an autoimmune inflammation of the thyroid.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study also indicated that the TSH in HT patients was higher than that in patients with PTC alone. These results were consistent with many other previous observations ( 24 , 30 ). HT, which is characterized by the infiltration of abundant lymphocytes, fibrosis, and parenchymal atrophy of thyroid tissue, is an autoimmune inflammation of the thyroid.…”
Section: Discussionsupporting
confidence: 94%
“…However, an overly aggressive dissection that may damage the normal function of the RLN is not necessary ( 37 ). Therefore, the accurate identification of risk factors of CLNM is helpful to evaluate the status of CLN and determine the necessity of lymph node dissection, especially for PTC patients with HT ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also indicated that the TSH in HT patients was higher than that in patients with PTC alone. These results were consistent with many other previous observations (24,30). HT, which is characterized by the infiltration of abundant lymphocytes, fibrosis, and parenchymal atrophy of thyroid tissue, is an autoimmune inflammation of the thyroid.…”
Section: Discussionsupporting
confidence: 94%
“…A meta-analysis of 71 studies, which included 44034 patients, showed that thyroid cancer with or without lymph node involvement is much less common in patients with Hashimoto’s thyroiditis. Hashimoto’s thyroiditis also reduces the risk of cancer recurrence in patients operated on for malignant tumors of the thyroid gland ( 27 , 28 ).…”
Section: Central Lymph Node Dissection and Its Advantagesmentioning
confidence: 99%